1981
DOI: 10.1056/nejm198102263040901
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation during Cardiopulmonary Bypass

Abstract: We observed complement activation in 15 adults undergoing total cardiopulmonary bypass. Plasma levels of C3a were significantly elevated (P < 0.0001) at the beginning of the procedure, and they continued to increase steadily thereafter. At the end of the procedure, C3a levels were more than five times higher than preoperative levels. Plasma levels of C5a (a factor that binds avidly to neutrophils) did not change significantly during cardiopulmonary bypass. Instead, there was significant neutrophilia (P = 0.03)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
90
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,038 publications
(92 citation statements)
references
References 17 publications
2
90
0
Order By: Relevance
“…Our observation that plasma levels of C3a were higher than those of C5a confirms previous reports of these values in other diseases (10)(11)(12). This result may be due to at least 2 factors that relate to production and clearance of these cleavage products.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observation that plasma levels of C3a were higher than those of C5a confirms previous reports of these values in other diseases (10)(11)(12). This result may be due to at least 2 factors that relate to production and clearance of these cleavage products.…”
Section: Discussionsupporting
confidence: 91%
“…While C3a and C5a are rapidly converted by plasma carboxypeptidase N to desArg forms, which lack anaphylatoxin activity, it is important to note that C3a desArg and C5a desArg retain the capacity to activate platelets ( 5 ) and neutrophils (7,8), respectively. Indeed, the aggregation of these cells in small vessels upon exposure to C3a and C5a is believed to play a central role in the development of the tissue injury observed during endotoxic shock (14), adult respiratory distress syndrome (23), and LCrebral injury after cardiopulmonary bypass (12). It is therefore not unlikely that in some SLE patients, the exposure of neutrophils and platelets to these complement-derived mediators would be a cause of significant vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that complement activation occurs during CPB ( 1-4). Additionally, the role of complement in the associated morbidity and mortality has been indirectly demonstrated in a number of studies (42)(43)(44), where indices of cardiac and pulmonary dysfunction in adults and multisystem organ failure in infants and children correlated significantly with complement activation. However, the exact role of the various activated complement products such as C3a, C3b, C5a, and CSb-9 in the induction of many of the specific cellular changes associated with CPB is ill-defined because of the paucity of effective complement inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, regardless of the mechanism which leads to their production, the complement-derived anaphylatoxins generated in the plasma of patients with active SLE are potential inflammatory mediators: C3a des Arg and C5a desArg activate platelets (29) and neutrophils (30), respectively. Aggregation of these cells in small vessels following exposure to C3a desArg and C5a desArg has been invoked as a cause of vascular injury in diverse clinical syndromes including the adult respiratory distress syndrome (3 l), cerebral injury following extracorporeal circulation (32,33), reperfusion injury of the myocardium (34,35), and endotoxic shock (36). We have recently provided serologic and histologic evidence which suggests that syndromes of reversible hypoxemia and cerebritis in SLE may have a similar pathogenic mechanism (37).…”
Section: Discussionmentioning
confidence: 99%